The growth in newspaper coverage of tobacco control in China, 2000-2010 - Gao Junling; Chapman Simon; Sun Shaojing; Fu Hua; Zheng Pinpin (BMC, 2012)
Abstract Background Media coverage of tobacco-related issues can potentially shape individual beliefs, attitudes and behaviors about tobacco use. This study aims to describe news coverage of tobacco control related issues in Chinese newspapers from 2000 to 2010. Methods All 1149 articles related to tobacco control were extracted from the Database of Chinese Important Newspapers and content analyzed for the period Jan 1, 2000 to Dec 31, 2010. The changing pattern of tobacco control topic, article type, viewpoint, and article origin, and their relationship were analysed. Results News coverage of tobacco control related issues increased significantly (p < 0.01) from 2000 to 2010, with news coverage being relatively intensive in May and June (p < 0.01), around World No Tobacco Day. 24.9% (n = 286) of all articles focused on secondhand smoke, 25.3% (n = 291) warned about the dangers of active smoking, and 10.0% (n = 115) focused on prevention and cessation programs and campaigns. Tobacco control topics varied significantly between national vs city/regional newspapers (χ2 = 24.09, p = 0.002) and article types (χ2 = 193.35, p < 0.001). Articles in national newspapers had more coverage of the dangers of tobacco and on enforcing bans on tobacco-advertising. News stories centered around monitoring tobacco use and smoke free activity, while editorials focused on enforcing bans on tobacco-advertising, youth access and programs and campaigns. Letters to editors focused on the dangers of smoking, raising tax, and smoking cessation. More articles (50.4%) took an anti-tobacco position (compared with 10.5% which were pro-smoking), with the amount of negative coverage growing significantly across the decade. National articles tended to lean toward anti-tobacco, however, local articles tended mix of pro-tobacco and neutral/balance positions. Editorials seemed to be more anti-tobacco oriented, but letters to the editor tended to show a mix of anti-tobacco and pro-tobacco positions. Conclusion Chinese newspapers are giving increasing attention to tobacco control, but coverage remains lower than in the USA and Australia. Health workers need to give higher priority to efforts to increase news coverage beyond the present concentration around World No Tobacco Day and to develop strategies for making tobacco control issues more newsworthy to both national and local news outlets.